Young woman with Multiple Endocrine Neoplasia 2B (MEN 2B) Diagnosed by PET-CT-A Case Report - Afrin, Rawnak; Biswas, Shankar; Sharmin, Shaila; Mostofa, ABM Golam; Haque, Jasmine Ara (Bangladesh Journal of Nuclear Medicine, 2022)
Multiple endocrine neoplasia, type 2B (MEN2B) is an autosomal dominant syndrome characterized by medullary thyroid carcinoma, pheochromocytoma, multiple mucosal neuromas & intestinal ganglioneuromas. A young woman of 20 years presented with irregularity of both lips since childhood and a midline neck swelling which gradually increased in size within last 1 year. She had hypertension and history of three episodes of paroxysmal spells characterized by headache, palpitations and excessive sweating during past 5 months. On physical examination, patient was having tachycardia, high blood pressure level (140/100 mmHg), sweaty with no tremor or exophthalmos. She had bumpy lips, multiple mucosal neuromas in lip & buccal mucosae, a hard nodular goiter and no marfanoid habitus. Core biopsy from right thyroid lobe revealed medullary thyroid carcinoma. Calcitonin level were markedly elevated. 18F-FDG PET-CT scan showed heterogeneous mixed density soft tissue mass involving both lobes and isthmus of thyroid gland with intense FDG uptake and FDG avid enlarged right cervical lymph nodes. A well circumscribed complex mass was found in the left upper abdomen adjacent to pancreas. Left adrenal gland showed a heterogeneous mass with mild FDG uptake and according to PET-CT findings, patient was diagnosed as a case of MEN 2B. Bangladesh J. Nuclear Med. 24(1&2): 60-63, 2021